Supporting Family-Centered Practice through Supervision: An Evaluation of Strengths-Based Supervision. Issue 4 (October 2014) - Lietz, Cynthia A.; Hayes, Megan J.; Cronin, Travis W.; Julien-Chinn, Francie
Strengths-based supervision (SBS) is a model of clinical supervision that was developed to support effective implementation of family-centered practice in public child welfare. An evaluation was conducted to determine the degree to which learning from this 2-day workshop transferred to changes in supervisory practices. Links to pre- and posttest anonymous online surveys were sent through email to the supervisees of the supervisors who participated in the SBS training. Findings suggest that 41% of respondents reported positive changes to the supervision they received in child welfare after their supervisors attended the training. Changes that were discussed in open-ended comments were consistent with the training content. Findings offer implications regarding the benefit of this training for supervisors working in child welfare settings.